Effect of the Conditioned Medium from H9C2 Cell Line Treated with Dehydroepiandrosterone and Exposed to Damage on the Motility of Mesenchymal Stem Cells - Castro Santos, G. X.; Salas Medina, J. L.; López Marure, R.; Cáceres Cortés, J. R.; Parra Barreraa, A.; Mera Jiménez, E.; Gutiérrez Iglesias, G. (Revista Mexicana de Ingenieria Biomedica, 2017)
Cardiovascular diseases (CVD) are the leading cause of death worldwide. Mesenchymal Stem Cell (MSC) therapy is an alternative for patients who cannot recover with current treatments. Ensure movilization of MSC to the affected organs would represent an advantage for therapeutic management of CVD. Dehydroepiandrosterone (DHEA) is a hormone precursor whose levels decrease throughout life, which has been associated with the onset of CVD. Several studies have shown that DHEA consumption, prevents and improves heart condition, although it is not known if this is because an effect on cardiomyocytes is exercised on these cells and this, in turn, to CTM. The aim of this study was to determine the effect of conditioned medium from H9C2 cell line pretreated with DHEA and subjected to damage, on the motility of CTM, performing a wound healing assay. Pretreatment with DHEA and damage to H9C2 cell line, promotes motility of CTM. Stimulation of CTM motility by an indirect effect of DHEA could be a therapeutic strategy for heart damage.